MANAJEMEN SEKOLAH UNTUK MENINGKATKAN MUTU AKADEMIK DAN NON AKADEMIK LULUSAN DI SMAN 1 BANJARAN KABUPATEN BANDUNG - Ratnawulan, Teti; Suwandari, Lilis; Nurhasanah, Intan; Meliyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of POAC management functions (planning, organizing, actuating, and controlling) in improving graduate quality at SMA Negeri 1 Banjaran. The research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and document analysis. The findings indicate that the planning stage was systematically formulated through the establishment of graduate quality standards, curriculum development, and planning for the improvement of human resources and facilities. Organizing was implemented through a clear division of roles and responsibilities within the school structure. The actuating stage was characterized by collaborative leadership, the implementation of academic and non-academic programs, and continuous teacher professional development. Controlling was conducted through regular evaluations of academic and non-academic outcomes. Overall, the implementation of POAC management functions was effective and contributed positively to improving the quality of graduates..